2020
DOI: 10.1039/c9fo02939g
|View full text |Cite
|
Sign up to set email alerts
|

Resistant starch type-2 enriched cookies modulate uremic toxins and inflammation in hemodialysis patients: a randomized, double-blind, crossover and placebo-controlled trial

Abstract: The study evaluated the effect of resistant starch enriched cookies supplementation on the mRNA expression of nuclear transcription factors involved with inflammation and uremic toxins levels produced by the gut microbiota in hemodialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…[ 24 ] Also, RS2 was able to increase the messenger ribonucleic acid (mRNA) nuclear erythroid 2‐related factor (Nrf2) and NAD(P)H quinone dehydrogenase 1 (NQO1) protein expression, which are related to anti‐inflammatory and anti‐oxidative stress mechanisms. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Also, RS2 was able to increase the messenger ribonucleic acid (mRNA) nuclear erythroid 2‐related factor (Nrf2) and NAD(P)H quinone dehydrogenase 1 (NQO1) protein expression, which are related to anti‐inflammatory and anti‐oxidative stress mechanisms. [ 25 ]…”
Section: Introductionmentioning
confidence: 99%
“…In a study with CKD rats, RS attenuated the inflammation [67]; however, in clinical studies, the results are still discordant. While, in one study, a reduction in some inflammatory markers was observed (TNF-α and IL-6) [68], in another, with the same dose of RS, no difference was found in the levels of hsCRP and IL-6 of HD patients [36]. Some limitations and strengths of the present study should be acknowledged.…”
Section: Discussionmentioning
confidence: 60%
“…Regarding the other two gut-derived uremic toxins evaluated (pCS and IAA), no impact of UBF was observed. Similarly, no difference in the serum total pCS was observed in other RS intervention studies with HD patients [34,36]. In healthy individuals, the production of IS and pCS does not seem to be correlated [28], suggesting that the regulation of their production occurs by different factors.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…NRF2 null mice have exaggerated and accelerated kidney injury, and conversely, NRF2 activating supplements have been shown to improve kidney function (as reviewed in [38]). Studies in patients with end stage renal dis-ease have shown increased NRF2 expression in response to dietary interventions, including administration of starch-enriched cookies [39], and brazil nut supplementation [40], though these studies did not correlate these NRF2 expression changes with clinical measures. A third pilot study involving curcumin showed no change in NRF2 mRNA expression [41].…”
Section: End-stage Renal Diseasementioning
confidence: 96%